2021
DOI: 10.17049/ataunihem.930846
|View full text |Cite
|
Sign up to set email alerts
|

Hemşi̇releri̇n İş Stresi̇ Ve Tükenmi̇şli̇k Düzeyleri̇ İle Meslek Ve Yaşam Doyumu Düzeyleri̇ Arasindaki̇ İli̇şki̇ni̇n Beli̇rlenmesi̇

Abstract: Determination of The Correlation of Job Stress and Burnout Levels of Nurses with Their Job and Life Satisfaction LevelsAim: This study was conducted with descriptive and cross-sectional design to determine the correlation between the job stress, burnout, job and life satisfaction levels of nurses. Methods: The study was carried out in public hospital between September-November 2020. It was aimed to reach the all population, no sampling method was used. The data were collected from 642 voluntary nurses using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…In other words, with mindfulness, awareness of the problems caused by stress is increased, allowing the person to quickly return to a state of balance. (13,14). Mindfulness helps individuals become aware of their negative thoughts and enables them to accept their stressful emotions and thoughts in accordance with the "here and now" principle.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, with mindfulness, awareness of the problems caused by stress is increased, allowing the person to quickly return to a state of balance. (13,14). Mindfulness helps individuals become aware of their negative thoughts and enables them to accept their stressful emotions and thoughts in accordance with the "here and now" principle.…”
Section: Introductionmentioning
confidence: 99%
“…Hemşireler, uzun çalışma saatleri nedeniyle, yorgunluk yaşamışlar ve aynı zamanda sürekli maske takmaya bağlı olarak göğüs sıkışması, baş ağrısı ve yüksek sesle konuşma durumunda kalmışlardır. Buna ek olarak, koruyucu önlükler hemşirelerde alerji riskini artırmıştır (Bayülgen ve ark., 2021;Camcı & Kavuran, 2021;Cebeci & Kara, 2021). Ayrıca, psikolojik ve sosyal destek ihtiyacı yeterince karşılanmamış, özlük haklarıyla ilgili sorunlar yaşanmıştır (Hiçdurmaz & Üzar-Özçetin, 2020;Yıldırım & Çetin, 2020).…”
Section: Introductionunclassified
“…1 Studies have shown that nursing is also a stressful profession. 2,3 In this regard, it is important to determine the personality characteristics nurses possess. According to Beck et al; 4 Beck (1983) mentions two personality dimensions in their cognitive theory; autonomy and sociotropy (social belonging).…”
Section: Introductionmentioning
confidence: 99%